Disease-modifying therapies for Alzheimer’s disease: Clinical trial progress and opportunity - Zhang, Yujie; Chen, Jie; Li, Yanru; Jiao, Bin; Luo, Shilin (Ageing research reviews, 2025)
The U.S. Food and Drug Administration (FDA) recently approved lecanemab and donanemab for the treatment of early symptomatic Alzheimer's disease (AD) after their phase III trials reached endpoints. These two anti-amyloid β monoclonal antibodies represent the latest promise of disease-modifying therapy (DMT) for AD, which undoubtedly reignites new hope for DMTs to combat the staggering financial and human costs of AD. However, in addition to these two successful antibodies, there have been enormous efforts to develop DMTs in various aspects to meet the therapeutic requirement of AD. In this review, we delineate the core principles and methodologies of diverse DMTs, covering the advances in clinical trials of drug candidates that either have been discontinued, completed, or are ongoing, as well as brain stimulation and lifestyle interventions. In addition, by overseeing the fate of various candidate molecules, we hope to provide references and ideas for prospective approaches and promising applications of DTMs for AD, particularly in terms of universality and clinical application economics, to optimize efficacy and maximize AD patient benefits in the future. •The clinical trial performance of anti-amyloid β monoclonal antibodies gives promise of disease-modifying therapy for AD.•The core principles and methods of different DMTs and the fate of related clinical trials for AD are reviewed.•The prospective pathways and promising utilization of DMTs for AD in future scenarios are contemplated.